How can basic services be provided in poor communities? - Villao, Datzania (Revista Científica y Tecnológica UPSE, 2016)
Despite some authors contesting that participation makes no difference, community participation is important for policy implementation. However, in order to community participation can be effective, people have to participate in all levels of a project.This article examines how sanitation services, can be provided in poor communities. The paper examines the case of “Salud Para el Pueblo” (SPP), a project that provided sanitation services in Santa Elena –Ecuador with the active participation of the community. The paper argues that to increase the provision of water and sanitation services, it is necessary to include the community in the planning, design, implementation and maintenance of the project. The article examined the literature about community participation and related it to the community participation in SPP. As a result of the involvement of the community, the project reflected community´s real needs, increased their accountability, reduced costs of the project and also contributed to better health in Santa Elena.